QUALITY ENHANCEMENT OF HIGHER EDUCATION IN CAMBODIA - Chheng, Dr. Ly (Srawung: Journal of Social Sciences and Humanities, 2024)
Quality improvement is critical for both public and private colleges in Cambodia. The purpose of this study is to identify common quality management practices in Cambodian Higher Education Institutions (HEIs), measure the relationships between quality management and quality assessments (internal and external), and evaluate the relationships between quality assessments and HE quality enhancement. A quantitative research approach was used in this study to evaluate the factors between quality enhancement and quality management for their significant implications. This study used simple and multivariate regressions to look at how quality assurance variables affect higher education quality. The study developed accurate questionnaires for 337 people from Cambodia's private and public higher education colleges and institutes, including academics and management staff. According to the findings, the majority of institutions regarded academic curriculum, facilities, educational management, academic staff and teaching methodologies, and student evaluation as critical quality management measures. However, they placed less emphasis on cooperation. The multiple regression analysis revealed that factors related to internal quality assessment (IQA), external quality assessment (EQA), and HE quality enhancement were consistent, indicating that academic curriculum, student assessment, facilities, support staff, and collaborations were potential factors for improving higher education quality. The emphasis on Internal Quality Assessment (IQA) and External Quality Assessment (EQA) resulted in dramatically enhanced higher education quality. Highly ranked institutions tended to have a better IQA and EQA system, and IQA and EQA played an important role in conducting frequent examinations of quality management methods.